Observation and analysis of a classroom teaching and learning practice based on augmented reality and serious games on mobile platforms - Sylvie Barma; Sylvie Daniel; Nathalie Bacon; Marie-Andrée Gingras; Mathieu Fortin (Serious Games Society, 2015)
This qualitative research is part of a learning effort to better understand how serious games are exploited in a science education context. The research team examined this issue by focusing on augmented reality as a technological innovation imbedded on a tablet. Given the current state of knowledge related to serious games and augmented reality, and given the fact that its use in the context of teaching/learning is not extended, this paper focuses on an initial exploration of how a new teaching practice involving a serious game based on an interactive augmented reality solution would impact on students in a physics class. A Design Based Research methodology was applied in a real‑world context within a college‑level physics class. Two conceptual tests containing ten questions on spatial notions regarding electromagnetic fields were administered to two control groups and two groups using the proposed serious game. The latter groups were administrated a game evaluation questionnaire as well. Thematic interpretation of students written responses to the evaluation questionnaire as well as the lessons and observations we derived from the in-class experimentation are provided and discussed in the paper.